Rediscovery and conservation status of six short‐range endemic Pseudanophthalmus cave beetles (Carabidae: Trechini). Issue 6 (13th September 2017) - Niemiller, Matthew L.; Zigler, Kirk S.; Ober, Karen A.; Carter, Evin T.; Engel, Annette S.; Moni, Gerald; Philips, T. Keith; Stephen, Charles D. R.
Abstract: The North American endemic cave beetle genus Pseudanophthalmus is exceptionally diverse, with >150 described taxa in karst regions of the eastern United States. Eighty‐seven per cent of taxa, however, are at risk of extinction due to small, restricted distributions, low abundance, and several potential anthropogenic threats to their habitats. Six species in Tennessee are exceedingly rare and are candidates for listing under the U.S. Endangered Species Act: Coleman Cave Beetle ( P. colemanensis ), Fowler's Cave Beetle ( P. fowlerae ), Inquirer Cave Beetle ( P. inquisitor ), Bakers Station Cave Beetle ( P. insularis ), Noblett's Cave Beetle ( P. paulus ), and Soothsayer Cave Beetle ( P. tiresias ). Each species is an extreme short‐range endemic. Four species have not been observed in several decades, and two species ( P. insularis and P. paulus ) are considered possibly extinct. We searched 57 caves in 15 counties in Tennessee, including eight of the nine historical localities of the six Pseudanophthalmus species between July 2013 and March 2016 to determine if populations were still extant, to search for new populations, and to estimate relative abundance. We confirmed the continued existence of all six species, including P. fowlerae, P. insularis, P. paulus, and P. tiresias, which had not been observed in 52, 60, 50, and 42 years, respectively. We also discovered five new populations in total, one for each species except for P. paulus . Although U.S. Fish and Wildlife Service ruled that all six species do not warrant federal listing, all species continue to have restricted ranges and remain at an elevated risk of extinction.